2023
DOI: 10.1212/wnl.0000000000201630
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change and Air Pollution on Neurologic Health, Disease, and Practice

Abstract: Background and objectives:Although the international community collectively seeks to reduce global temperature rise to under 1.5ºC before 2100, irreversible environmental changes have already occurred, and as the planet warms these changes will continue to occur. As we witness the effects of a warming planet on human health, it is imperative that neurologists anticipate how the epidemiology and incidence of neurologic disease may change. In this review, we organized our analysis around three key themes related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 54 publications
3
24
0
3
Order By: Relevance
“…Two recent publications have briefly reviewed associations between air pollution and headache and/or migraine 13,55 . The overall conclusions of these papers are in agreement with our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Two recent publications have briefly reviewed associations between air pollution and headache and/or migraine 13,55 . The overall conclusions of these papers are in agreement with our results.…”
Section: Discussionsupporting
confidence: 92%
“…The overall conclusions of these papers are in agreement with our results. A scoping review that included a summary of air pollution and headache 55 reported point estimates above the null value for associations between migraine outcomes and carbon monoxide, nitrogen dioxide, ozone, PM 2.5 , and PM 10 . A recent narrative review of air pollution and headache disorders 56 cited 10 studies in total in relation to headache.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Louis et al 7 for advancing in our knowledge of this topic. The information they provide may help in our efforts to protect and improve the neurologic health of our communities and our world!…”
mentioning
confidence: 97%
“…5 Modeling studies indicate that the economic value of health cobenefits from improved air quality may exceed the entire cost of the measures needed to mitigate climate change. 6 In this issue of Neurology, Louis et al 7 have advanced our educational mission with their scoping review of articles dealing with the association of climate change and human neurologic disorders. They grouped the articles into consequences of extreme weather, neuroinfectious diseases, and pollution impacts.…”
mentioning
confidence: 99%
See 1 more Smart Citation